Essential RenderMan® - Stephenson, Ian (Springer London : Imprint: Springer, 2007)
RenderMan has long been associated with top-end film production and is an essential tool for creating many of the effects and images in recent animated films (such as Monsters, Inc., Finding Nemo and The Incredibles). RenderMan is widely available and, with the demand for higher quality images, is now used by computer-based artists at all levels of the graphics industry. Intended to provide a straightforward and easy introduction to the basic techniques involved, this book provides an excellent grounding, enabling readers to confidently move to more advanced texts. This second edition includes a new chapter on global illumination, and, with plenty of illustrations and hands-on examples, Ian Stephenson: • gives an overview of RenderMan • explains how scenes are described • illustrates (among other things) how to create surfaces; colour; lighting; shadows; and depth of field, using RIB and the C API • introduces the techniques involved in creating shaders, applying textures and using global illumination.